2014
DOI: 10.1111/crj.12129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of peramivir in adult patients with seasonal influenza during the winter of 2012 in Japan

Abstract: The clinical efficacy of peramivir is non-inferior to that of oseltamivir, although peramivir tended to be used in patients with serious complications. Intravenous administration of peramivir may be useful for patients with serious complications, such as consciousness disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…The treatment was chosen by the physician in accordance with the patient’s medical condition. No significant difference was found between the peramivir (30.9 hours) and oseltamivir (34.7 hours) groups in terms of the median time to defervescence 50. Peramivir appeared to be as efficacious as oseltamivir.…”
Section: Resultsmentioning
confidence: 73%
“…The treatment was chosen by the physician in accordance with the patient’s medical condition. No significant difference was found between the peramivir (30.9 hours) and oseltamivir (34.7 hours) groups in terms of the median time to defervescence 50. Peramivir appeared to be as efficacious as oseltamivir.…”
Section: Resultsmentioning
confidence: 73%
“…Additional clinical trials, including open-label randomized trials as well as retrospective observational studies, are provided in Table 4 9,5355,60…”
Section: Clinical Efficacy and Comparative Trials Of Peramivirmentioning
confidence: 99%
“…Additional studies have demonstrated the clinical effects of peramivir in adult patients 53,54. An open-label, randomized trial of hospitalized patients of ≥6 years of age was conducted by Ison et al54 to determine viral titer decline between two peramivir regimens.…”
Section: Clinical Efficacy and Comparative Trials Of Peramivirmentioning
confidence: 99%
“…Different NAI formulations have been developed to provide more treatment options for management of influenza. Peramivir, the first antiviral agent to be approved for intravenous administration in Japan and South Korea in 2010 and also approved in the USA in 2014, is intended to provide rapid control of progressive influenza in patients with serious complications [2]. A single administration of peramivir once daily was able to achieve treatment by stable binding with NA with the N9 subtype in a mouse model [3].…”
Section: Introductionmentioning
confidence: 99%